Strategi Komunikasi Pemasaran Pariwisata Taman Raja Batu Dalam Meningkatkan Arus Pariwisata Di Kabupaten Mandailing Natal - Adriani Putri Shafira Nasution; Syafruddin Ritonga; Taufik Wal Hidayat (Jurnal Antropologi Sumatera, 2022)
The aim of the research is: to find out how the marketing communication strategy of Taman Raja Batu is in increasing the flow of tourism in Mandailing Natal Regency. To find out what factors hinder the tourism marketing communications of Taman Raja Batu in increasing the flow of tourism in Mandailing Natal Regency. The marketing communication strategy for Taman Raja Batu Tourism carried out by the Mandailing Natal Regency Tourism Office through various forms of promotion both internally and externally, in the form of promotion through social media which primarily targets young people and adolescents, bearing in mind that in the millennial era as when These young people and teenagers are inseparable from social media Facebook and Instagram. The inhibiting factors in tourism marketing communication at Raja Batu Park in increasing the flow of tourism in Mandailing Natal Regency are very minimal tour guides, so they are unable to create good communication in every introduction to tourist objects. The Tourism Office in increasing the flow of the tourism sector in Mandailing Natal Regency as the manager, lack of awareness, mindset and participation of the community's role in every activity in Taman Raja Batu Tourism.